Pengaruh kualitas Produk, Harga, dan Citra Merek terhadap Keputusan Pembelian Konsumen Cimory di Kecamatan Juwiring Klaten - Mirna Bungasari; Sumaryanto Sumaryanto (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of product quality, price, and brand image on consumers' purchasing decisions of Cimory products in Juwiring District, Klaten. This research employed a quantitative approach with primary data obtained directly from respondents through questionnaires. The sampling technique used was purposive sampling with a total of 100 respondents. Data analysis techniques included multiple linear regression, t-test, F-test, and coefficient of determination (R²). The regression equation obtained was Y = 0.731 + 0.567X₁ + 0.195X₂ + 0.215X₃ + e. The t-test results showed that product quality (t = 7.537; sig. 0.000), price (t = 2.570; sig. 0.012), and brand image (t = 3.404; sig. 0.001) each had a significant effect on purchasing decisions of Cimory consumers in Juwiring District, Klaten. The F-test results showed an F-value of 119.729 with a significance of 0.000 (< 0.05), indicating that the three variables simultaneously had a significant effect on purchasing decisions. The Adjusted R Square value of 0.783 indicated that product quality, price, and brand image explained 78.3% of the variation in purchasing decisions, while the remaining 21.7% was explained by other variables outside the research model, such as promotion.